Improved survival of patients with newly diagnosed oligometastatic prostate cancer through intensified multimodal treatment - Schütz, Viktoria; Nessler, Christopher-Leo; Duensing, Anette; Zschäbitz, Stefanie; Jäger, Dirk; Debus, Jürgen; Hohenfellner, Markus; Duensing, Stefan (Frontiers in Oncology, 2024)
Background and objectivesThe standard of care for patients with metastatic hormone-sensitive prostate cancer (mHSPC) includes androgen deprivation therapy (ADT), novel antihormonal therapies (NHT) and/or chemotherapy. Patients with newly diagnosed oligometastatic prostate cancer (omPCa) represent a distinct subgroup of mHSPC, for which the optimal treatment, particularly the role of radical prostatectomy (RP) and metastasis-directed therapy (MDT), is currently under debate.Materials and methodsIn this single center, retrospective analysis, 43 patients with newly diagnosed omPCa were included. All patients underwent RP as part of a multimodal, personalized treatment approach. Other treatments included ADT, NHT, MDT (surgery or radiotherapy), adjuvant radiotherapy (prostatic fossa and/or pelvic lymph nodes) or chemotherapy in various combinations. Clinical endpoints were progression free and cancer specific survival (PFS, CSS).ResultsNo patient with omPCa died from prostate cancer during an up to ten years follow-up period after intensified multimodal treatment i.e., RP, ADT, adjuvant radiation therapy and MDT (n=13). In contrast, patients requiring chemotherapy (n=10) showed a significantly worse PFS (p<0.001) and CSS (p<0.001). Patients receiving various combinations (<4 therapeutic modalities; n=20) showed a more favorable outcome than patients receiving chemotherapy, but differences in PFS and CSS were not statistically significant compared to patients receiving an intensified multimodal treatment.ConclusionsAn intensified, multimodal treatment approach including RP can lead to excellent survival outcomes in patients with newly diagnosed omPCa. Patients requiring chemotherapy have most likely a more aggressive disease and therefore a more rapid tumor progression. Future studies to identify markers for risk stratification in patients with omPCa are therefore needed.